SimTube: A National Simulation Training and Research Project - Wiet, Gregory J; Deutsch, Ellen S; Malekzadeh, Sonya; Onwuka, Amanda J; Callender, Nathan W; Seidman, Michael D; Fried, Marvin P (Otolaryngology-head and neck surgery, 2020)
To test the feasibility and impact of a simulation training program for myringotomy and tube (M&T) placement. Prospective randomized controlled. Multi-institutional. An M&T simulator was used to assess the impact of simulation training vs no simulation training on the rate of achieving competency. Novice trainees were assessed using posttest simulator Objective Structured Assessment of Technical Skills (OSATS) scores, OSATS score for initial intraoperative tube insertion, and number of procedures to obtain competency. The effect of simulation training was analyzed using χ tests, Wilcoxon-Mann-Whitney tests, and Cox proportional hazards regression. A total of 101 residents and 105 raters from 65 institutions were enrolled; however, just 63 residents had sufficient data to be analyzed due to substantial breaches in protocol. There was no difference in simulator pretest scores between intervention and control groups; however, the intervention group had better OSATS global scores on the simulator (17.4 vs 13.7, = .0003) and OSATS task scores on the simulator (4.5 vs 3.6, = .02). No difference in OSATS scores was observed during initial live surgery rating ( = .73 and = .41). OSATS scores were predictive of the rate at which residents achieved competence in performing myringotomy; however, the intervention was not associated with subsequent OSATS scores during live surgeries ( = .44 and = .91) or the rate of achieving competence ( = .16). A multi-institutional simulation study is feasible. Novices trained using the M&T simulator achieved higher scores on simulator but not initial intraoperative OSATS, and they did not reach sooner than those not trained on the simulator.